Mechanism of IL‑8‑induced acute lung injury through pulmonary surfactant proteins A and B - Yang, Yinong; Li, Qing; Tan, Feng; Zhang, Jun; Zhu, Wu (Experimental and therapeutic medicine, 2020)
This study explored how interleukin-8 (IL-8) causes acute lung injury (ALI) through pulmonary surfactant protein A (SP-A) and surfactant protein B (SP-B). Serum was collected from 53 ALI patients and further 56 healthy subjects who underwent physical examination. The IL-8, SP-A, and SP-B levels were determined using enzyme-linked immunosorbent assay (ELISA). An ALI model was constructed using lipopolysaccharide (LSP)-induced normal A549 cells. siRNA was employed to interfere with the expression of IL-8, SP-A and SP-B. Western blot analysis was carried out to determine the protein levels, and MTT assay to determine the cell activity. In addition, co-immunoprecipitation (Co-IP) assay was used to verify the interaction between IL-8, SP-A and SP-B. ALI patients showed high expression of serum IL-8, and low expression of SP-A and SP-B, and IL-8 was negatively correlated with SP-A and SP-B, respectively. LSP-induced normal A549 cells showed increased expression of IL-8 and decreased expression of SP-A and SP-B. Silencing IL-8 led to increased expression levels of SP-A, SP-B and Bcl2, decreased expression levels of caspase-9, caspase-3, Bax, TNF-α, IL-17 and IL-1β, reduced cell apoptosis rate, and enhanced cell viability. Silencing SP-A and SP-B resulted in increased expression of IL-8, caspase-9, caspase-3, Bax, TNF-α, IL-17 and IL-1β, and decreased expression of Bcl2. Co-IP assay revealed that IL-8 could interact with SP-A and SP-B, respectively. IL-8 induces apoptosis by inhibiting SP-A and SP-B, and intensifies cellular inflammatory reaction, leading eventually to ALI.